THU0227 Spinal fracture risk in ankylosing spondylitisin western australia. (12th June 2018) - Ognjenovic, M.; Raymond, W.; Keen, H.; Inderjeeth, C.; Preen, D.; Nossent, J.
Abstract : Background: In Ankylosing Spondylitis (AS) chronic spinal inflammation contributes to spinal osteoporosis and rigidity. Large scale studies on vertebral fractures in AS patients are scarce with rates reported between 0.4% and 32% 1–3 . While biological therapy for AS has been associated with better clinical outcomes, the long-term effect on spinal osteoporosis remains uncertain. Objectives: To longitudinally investigate population wide spinal fracture rates in AS patients and compare the risk, disease burden and survival rates between AS and age/gender matched controls. Methods: A case-control study sourced from linked health data on Emergency Department visits, Hospital Morbidity and Mortality Registry data for the period 1980–2015. Vertebral fractures prevalence (ICD-9: 733.13, 805X and 806X, ICD-10: M48.4X, M48.5X, M80.0X, S12.X, S22.X, S32.X), burden of disease and mortality were compared between AS patients (ICD-9: 720.0, ICD-10: M45X or M08.1) with up to 5 controls matched for age, gender, Indigenous status and event date. Results: We included 1285 AS patients (70% males) with mean age of 42.87±18.4 years at first event, followed for a median of 24 years. 19, 30 Spinal fractures were more frequent in AS patients than controls (52, 2.8% vs. 39, 0.6%, p=<0.0001, respectively), and among the AS patients, 27 (2%) had a single and 9 (0.7%) had multiple fractures. Thoracic fractures were most common (17, 33%), followed by cervical (10, 19%), lumbar (9, 17%), sacral and coccyx (4, 8%) and one unspecified vertebral fracture. Overall AS participants were at greater risk (OR: 4.78; 2.9, 7.7 CI) for spinal fractures than controls. The risk remained relatively consistent; ranging from OR: 4.72 (2.75, 8.08 CI) during 1980–89 to OR: 4.90 (1.68, 14.25 CI) throughout 1990–99. However, during 2000–2013, all 4 newly AS diagnosed patients experienced a total of 7 fractures compared to none in controls. Greater age at first hospital contact among AS patients increased the risk in having a vertebral fracture (OR: 1.035; 1.01, 1.05 CI), while presence of psoriasis and inflammatory bowel disease were not risk factors. Survival rates following vertebral fractures at end of follow-up (35 years) were significantly lower for AS patients, (92%, vs. 98.5%, p<0.0001) compared to controls. Conclusions: The absolute risk for spinal fractures in AS patients is 2.8%, which is nearly 5 times the risk in controls. The risk has not improved in the era of TNFi therapy and the associated increased mortality indicates that spinal fractures remain a severe complication of AS. References: [1] Sambrook PN Arthritis research & therapy: BioMed Central A17. [2] Montala N, Juanola X, Collantes E, Muñoz-Gomariz E, Gonzalez C, Gratacos J, et al. Prevalence of vertebral fractures by semiautomated morphometry in patients with ankylosing spondylitis. The Journal of rheumatology2011;38(5):893–897. [3] Klingberg E, Geijer M, Göthlin J, Mellström D, Lorentzon M, Hilme E, et al. Vertebral fractures in ankylosing spondylitis are associated with lower bone mineral density in both central and peripheral skeleton. The Journal of rheumatology. 2012;39(10):1987–1995. Acknowledgements: Supported by Arthritis Foundation of Western Australia, Charlies Foundation for Research and Data Linkage WA. Disclosure of Interest: None declared